Identification of Novel Inhibitors for TG2 (Tissue Transglutaminase) and DJ-1 (Protein Deglycase) against Parkinson's Diseases by Pharmacophore-based Approaches (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Parkinson’s disease (PD) is a one of the most common neurodegenerative disease affecting the central nervous system (CNS) characterized by the multitude of motor and non-motor clinical symptoms. The hallmark of PD motor manifestation include progressive tremor, rigidity, brady kinesia and postural instability. There are many protein involved in the progression of this dieses including TG2 and DJ-1 protein. The present is focused on finding the novel inhibitor based from phytochemicals catagory to inhibit activity of TG2 and DJ-1 protein. The Cheminformatics pipeline used which include ADMET analysis,pharmacophore modeling and molecular docking. Six best hit molecules were mapped with the E-pharmacophore features of TG2 and DJ-1 protein. These pharmacophore were further analysed by molecular docking, protein–ligand interactions and in silico ADMET studies. The molecular docking analysis revealed that hydroxywogonin and 2',3',5,7-Tetrahydroxy flavones had good binding energy and satisfied the Lipinski rule of five and had no toxicity.